The differential impact of size mismatch in live versus deceased donor kidney transplant. Issue 6 (27th April 2021) - Vinson, Amanda; Skinner, Tom; Kiberd, Bryce; Clark, David; Tennankore, Karthik
Abstract: Background: The impact of weight mismatch between donors and recipients (D‐R) undergoing living‐donor kidney transplant (LDKT) versus weight‐matched deceased donor kidney transplant (DDKT) is not established. Aim: To determine whether absolute weight mismatch between D‐R affects graft survival following LDKT and how this relates to graft outcomes with DDKT when D‐R are weight matched. Materials & Methods: We used multivariable Cox proportional hazards models and the Scientific Registry of Transplant Recipients to determine the association of weight‐mismatched D‐R (>50 kg, 30–50 kg or 10–30 kg ((D < R); (D > R) and <10 kg (D = R)) with death‐censored graft failure in US LDKT recipients from 2006 to 2017. We also explored outcomes relative to weight‐matched DDKT and finally, the impact of combined D‐R weight‐sex mismatch. Results: In LDKT, the risk of graft loss was highest in the setting of D < R (HR 1.28, 95% CI 1.05–1.56 for >50 kg difference relative to D = R); however, this was still lower risk than weight‐matched DDKT. D‐R sex and combined weight‐sex mismatch were only important for male recipients (HR 1.47, 95% CI 1.27–1.71 for a male recipient >30 kg larger than their female donor, relative to weight‐matched male donor‐male recipient). This remained superior to weight‐sex‐matched DDKT however. Conclusion: D‐R weight‐sex mismatch is important in LDKT; however, graft survival remains superior to proceeding with matched DDKT. Optimizing D‐R matching in LDKT could be facilitated through a national kidney‐paired donation registry. LDKT weight‐sex mismatch should not be deferred in favor of DDKT.